(untitled) (Fiep Bulletin - online, 2013)
The elderly population growth generates important social, cultural and political repercussions, attracting researchers’ attention of several areas of knowledge. In such a way, the practice of physical activities is becoming a crucial role. The way as the activities are developed, the stimulus and the orientations directed to the health promotion of the senior, will depend on the different combination of strategies that allow the obtainment of results of personnel satisfaction and social interaction, weighing up the diversity of possibilities of this population. Therefore, this work aimed at comprehend how music influences the accomplishment of physical activities in elderly groups. The methodology based itself on a qualitative research through case study, in qualitative, interpretative and descriptive approach, with six extension project senior participants of an Academic Center. It was utilized as instruments semi-structured interviews, field diary and observations instruments. The information analysis occurred in three levels: the first one, where was accomplished the meaning units rising; the second one, with the units’ organization by categories; and the third one, with the triangulation. In front of the results, was verified that when we associate good taste and style, regarding the repertoire choice and the movement accomplishment, we can promote pleasure sensations, satisfaction, happiness and tranquility feelings, stimulating to accomplish several proposed exercises in class. The music, as long as formalizes the action intention, is a permanent concentration source, being a powerful resource for the energy waste, and specially a stimulus to force and vitality for the old aged. It concludes that, in the interventions with seniors, is necessary to consider the music as a primordial element during the physical activities accomplishment. The music can take away their unpleasant sensations, causing a lot of motivation and integration, represented through the movements,singings, sounds and smiles, besides being a great companion, promoting happiness, motivation and integration in the movements execution.